2011
DOI: 10.15193/zntj/2011/76/162-172
|View full text |Cite
|
Sign up to set email alerts
|

Content of Macro- And Microelements, and Fatty Acids in Muscles of Salmon (Salmo Salar L.), Rainbow Trout (Oncorhynchus Mykiss Walb.), and Carp (Cyprinus Carpio L.)

Abstract: S t r e s z c z e n i e Celem badań było określenie różnic międzygatunkowych pod względem zawartości: Mn, Cu, Zn, Fe, Ca, Mg, Na i K oraz kwasów tłuszczowych w mięśniach ryb: pstrąg tęczowy (Oncorhynchus mykiss Walb.), karp (Cyprinus carpio L.) i łosoś (Salmo salar L.), zakupionych w sklepach na terenie Olsztyna. Na i K oznaczono metodą fotometrii płomieniowej. Pozostałe pierwiastki analizowano metodą AAS. Kwasy tłuszczowe oznaczono techniką chromatografii gazowej. Karp cechował się największą zawartością Mn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…As confirmed by research, muscle tissue is not the main site of Ca accumulation in fish as opposed to the fish scales, bones, and skin [3,47]. Our results on Ca accumulation in various tissues of common carp were in agreement with Brucka-Jastrzębska et al [48] and Łuczyńska et al [49]. have shown that the effect of the prebiotic on Ca absorption depends on the content of this mineral in the diet.…”
Section: Calcium Concentrationssupporting
confidence: 91%
See 1 more Smart Citation
“…As confirmed by research, muscle tissue is not the main site of Ca accumulation in fish as opposed to the fish scales, bones, and skin [3,47]. Our results on Ca accumulation in various tissues of common carp were in agreement with Brucka-Jastrzębska et al [48] and Łuczyńska et al [49]. have shown that the effect of the prebiotic on Ca absorption depends on the content of this mineral in the diet.…”
Section: Calcium Concentrationssupporting
confidence: 91%
“…Mg, like Ca and phosphorus (P), is necessary for bone mineralization and it accumulates in the greatest amounts in bones [52]. Our results regarding the level of Mg accumulation in various tissues were in line with Brucka-Jastrzębska et al [48], Brucka-Jastrzębska and Protasowicki [53], Brucka-Jastrzębska and Kawczuga [54], and Łuczyńska et al [49]. The results of the present study showed that the highest level of this mineral was detected in the skeleton of fish fed 1% GOS (2.51 g kg −1 d.w.), and was significantly higher compared control treatment (0% GOS)…”
Section: Magnesium Concentrationsupporting
confidence: 88%
“…Polak-Juszczak [15] ), Nile perch (178.0 mg kg -1 ). Gokoglu et al [16] reported that raw fillet of rainbow trout has very high Ca (632 mg kg -1 ) inversely Łuczyńska et al [17] determined a lower Ca content in rainbow trout and salmon (137 mg kg -1 and 90 mg kg -1 , respectively) bought on Polish markets. This study found that both Ca and P content in liver and muscle of brown trout decreased in high stocking density.…”
Section: Resultsmentioning
confidence: 99%
“…In Poland, the most often consumed fish species are herring, pike, carp, and cod, which contain 32, 20, 10, and 9 mg Ca/100 g, respectively. Łuczyńska et al [ 26 ] measured more than 2 and 3.5 times more Ca in the muscles of carp and trout from Polish fisheries than in Ca derived from salmon muscle [ 26 ]. Carp and trout are very popular in Poland, especially during the Christmas season.…”
Section: Discussionmentioning
confidence: 99%